Determinasi Lingkungan Kerja, Disiplin Kerja, Budaya Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada Divisi Sales PT. Link Net. Tbk - Wahyu, Purnomo; Wibisono, Chablullah; Satriawan, Bambang (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze the influence of the work environment, work discipline, work culture and work motivation on employee performance with job satisfaction as an intervening variable in the Sales Division at PT. NetLink. Tbk. The research method used is a combined research method which is a research method between quantitative methods and qualitative methods to be used together in a research activity. The population in this study were employees of the Sales Division of PT. NetLink. Tbk which is spread throughout Indonesia with a total number of 960 people, while the number of samples in this study was 282 people, the questionnaire was distributed via the Google Form link with an estimated data collection for one month, after the data was collected it was then processed and analyzed further using using smartPLS 3.0 SEM (Partial Least Square-Structural Equation Modeling) software. The results of hypothesis testing on all independent variables show that work discipline, work culture, work motivation and work motivation have a significant effect on job satisfaction. Meanwhile, the work environment, job satisfaction, work discipline and work culture have no significant effect on employee performance. Furthermore, in this research, job satisfaction does not intervene in the influence of the work environment, work discipline, work culture and work motivation on employee performance.